AÇÕES AMBIENTAIS COM PESSOAS QUE CONVIVEM COM DEPRESSÃO EM UM CENTRO DE ATENÇÃO PSICOSSOCIAL - Fernandes, Marcelo Nunes da Silva; Peres, Paulo Edelvar Corrêa (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2011)
Search on a non-formal was developed by the therapeutic workshop reading of Psychosocial CareCenter 1 (CAPS 1) Sao Sepe / RS, aiming to get through debates and group dynamics of theelection of values about the environment and an awareness of the reality of our planet. Inaddressing the situation of the environment, we can see that through simple actions such as useof water in a conscious way, taking care of household waste separation and the correctdestination of the waste, among others, can contribute to the balance between man andenvironment, respect and care for life in different ways.